Analysis of lateral openings in tunnel linings. (August 2015) - Spyridis, Panagiotis; Bergmeister, Konrad
Highlights: Effects of basic parameters in tunnel breakout analysis and design are presented. Various tunnel openings analysis methods are comparatively investigated. A library of calculated stress patterns around tunnel openings is made available. Abstract: The present study discusses the structural response of a parent tunnel when a near circular breakout is made for a perpendicular child tunnel. Beyond the presentation of some main background on the topic, the description of the investigated systems and the investigation methods is provided, this mainly being linear-elastic finite elements analysis, with inclusion of analytical solutions for comparison and with some analysis assuming non-linear soil behavior in order to investigate particular aspects in the discussed systems. This paper contributes to the little hitherto available literature with respect to the soil structure-interaction and the structural behavior at tunnel breakouts and junctions, while reference for future projects is offered through 36 analyzed cases.